Distribution. Coastal waters of S South America from ¢.33° S in the Pacific Ocean and c.38° Sin the Atlantic Ocean, and S into Drake Passage (c.59° S) and Falkland Is. in Delphinidae - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
Distribution. Coastal waters of S South America from ¢.33° S in the Pacific Ocean and c.38° Sin the Atlantic Ocean, and S into Drake Passage (c.59° S) and Falkland Is. Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Delphinidae, pp. 410-526 in Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on page 490, DOI: 10.5281/zenodo.6610922